The nephron of swiftlet - an ultrastructural study - Lokman Hakim, Nur Liyana (2016)
It has been reported that the structural organization of the swiftlet nephron resembled that of the reptilian which was “loopless” – absence of the descending and ascending limbs of the loop of Henle. Being loopless and with a large cortex occupied mainly by the proximal tubules it is hypothesized that the swiftlet’s nephron is structurally simple but functionally efficient. Accordingly the present study examined the morphology of the swiftlet’s nephron at the ultrastructural level and towards this objective samples of the swiftlet’s kidney collected were processed for transmission electron microscopy. Numerous microvilli, a high incidence of mitochondria and an extensive indentation and infolding of the basal epithelium of the proximal tubule indicated enhanced reabsorption of glomerular filtrate and its release into peritubular capillary. Efficiency of the nephron is further augmented by the tubules of the intermediate segment which also showed similar structural evidences – microvilli, mitochondria and basal indentations and infoldings - indicating there was still considerable reabsorption of glomerular filtrate in this part of the nephric tubules. The distal convoluted tubules and collecting ducts also showed evidences of reabsorption and release of glomerular filtrate into peritubular capillary. An interesting observation in this study was the presence of many lipid droplets in the lumen of the nephron. Microvilli with dilated apical ends could be specially designed for the absorption of lipids in the intermediate segment. Thus the nephron of the swiftlet is simple as it is loopless but highly efficient as reabsorption take place throughout the entire length of the nephron.